Uma arquitetura orientada a serviços para redes de monitoração e atuação sem fio utilizando SOA - Araujo, Jeferson Martin de (Universidade Federal de São Carlos, 2008)
Research in sensor networks is widely regarded both as one of the most challenging and prospering area. Matching Computer Science concepts with Electrical Engineer applicability, Wireless Sensor and Actors Networks (WSAN) can be used to develop several case studies in manner to build applications which will be useful for evolving the WSAN s architecture, infra-structure and its components in general. Due to technologies advances reached by these scientific researches, the processing unities became exponentially more powerful with smaller size and lower cost, enabling the widespread use of the WSAN and making this technology more popular. So, it is clear that applications which depend on the WSAN s infrastructure to build system, in several applications domains, have been emerging. Actually, there are applications ranging from habitat monitoring to military purposes. One of the major problems associated with WSAN is the difficulty of developing software applications. Recent researches has shown that service oriented programming models may contribute to improve communication and interoperability between heterogeneous devices in pervasive spaces. Organizations seeking to develop WSAN applications can obtain a competitive advantage by developing applications on an architecture which supports reusability, maintainability and extendibility. Therefore, this work proposes the use of a service oriented approach for the development and management of applications specialized in remote area surveillance based on wireless and sensor networks characteristics and concepts.
Wireless sensor and actor networks; Service oriented architecture; Remote surveillance and monitoring; Application and solution architectures; Frameworks
Keywords: Arquitetura de redes de computadores; Arquiteturas distribuídas; Arquitetura - inovações tecnológicas; Arquitetura de software; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO